2010
DOI: 10.1002/14651858.cd007696.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the treatment of borderline ovarian tumours

Abstract: Background The safety of conservative surgery and the benefit of additional interventions after surgery for borderline ovarian tumours are unknown. Objectives To evaluate the benefits and harm of different treatment modalities offered for borderline ovarian tumours. Search methods We searched the Cochrane Gynaecological Cancer Group Trials Register to 2009, Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2008, Issue 4), MEDLINE and EMBASE to 2009. We also searched registers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…Faluyi showed that there was no difference in recurrence rate between cystectomy and USO (14). Chen found the same result from his research (15).…”
Section: Discussionsupporting
confidence: 52%
“…Faluyi showed that there was no difference in recurrence rate between cystectomy and USO (14). Chen found the same result from his research (15).…”
Section: Discussionsupporting
confidence: 52%
“…В заключении авторы не нашли фактов, подтвер-ждающих пользу от проведения дополнительных ме-тодов лечения, таких как химио-и лучевая терапия, при ПОЯ, и пришли к выводу, что ультраконсерватив-ные операции должны широко применяться в случаях двусторонних опухолей у больных, желающих сохра-нить фертильность [7].…”
Section: The Paper Discusses the Results Of Studies Conducted In Inteunclassified
“…Surgery is the backbone component of management either at diagnosis and when the recurrence is diagnosed. No alternative treatments have reported substantial activity: a recent Cochrane meta-analysis [12] on BOTs concluded that no evidence supports the use of any type of adjuvant chemotherapy in high-risk patients, and even if concern persists for patients with invasive peritoneal implants the effectiveness of this option continues to be debated. In contrast to high-grade serous ovarian cancer, different biological pathways seem to be involved in the carcinogenesis of MS-BOT and low-grade carcinoma, suggesting that targeted treatments should be used in this disease instead of chemotherapy [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic significance has been reported in several studies for peritoneal implants, especially invasive ones [32], and it has been postulated that the presence of invasive implants represents the most important risk factor for the transformation into invasive carcinoma [12], suggesting that these patients should be followed very closely. In our population, all patients with invasive implant developed recurrent disease differently from patients with non-invasive implants in which the recurrence appeared less frequently (100 vs. 62.5%) and delayed (28 vs. 46 months, respectively).…”
Section: Discussionmentioning
confidence: 99%